Nasi Bakar Menu Tradisional menjadi Menu yang Menasional - Widodo, Untung; Farizi, Sulaiman Al; Hihayat, Ibnu; Wijayanti, Maria Setya; Lumbantoruan, Mitra; Puspita, Mia (STIE Pelita Nusantara, 2024)
In Indonesia, there are many traditional foods that have almost disappeared from society. Because many contemporary food trends are appearing in society one after another, so traditional food has the potential to disappear and be forgotten by local people. Therefore, we took the initiative to preserve the local wisdom of traditional food typical of Sundanese, West Java, namely roasted rice. We will market this traditional food throughout Indonesia, especially on the island of Java. This grilled rice will be different from grilled rice in general. By creating and innovating grilled rice with various menu variations that are liked by all groups from children, teenagers, to adults, such as varying it with good quality chicken, sausages, meatballs and fish. By providing menu variations and new flavors in processing this grilled rice, we aim that this grilled rice food will be different from grilled rice in general. However, it will be a new high quality grilled rice with various variations and unique flavors that will be able to maintain the existence of grilled rice as a hitz food for Indonesian millennials and can be enjoyed by various groups. Seeing the opportunities from this business, we are sure to develop the simple grilled rice business to become better known to the wider community. Keywords: Grilled rice, innovation, menu variation